Local Wisdom Based Social Studies Learning for Strengthening Character Education in Elementary School Students - Imron Burhan (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2026)
This study aims to analyze and synthesize revious research related to local wisdom–based Social Studies learning as an effort to strengthen character education among elementary school students. This research employed a qualitative approach using a literature review design. The data were obtained from 15 scientific articles published between 2015 and 2025 and indexed in Google Scholar. The articles were selected through purposive sampling based on their relevance to the research topic and the availability of full-text access. Data collection was conducted through document analysis, and the data were analyzed using descriptive and thematic analysis to identify research trends and patterns related to the integration of local wisdom in Social Studies learning. The results indicate three main patterns. First, the integration of local wisdom into Social Studies learning materials and teaching strategies makes the learning process more contextual and meaningful. Second, local wisdom serves as a foundation for character education because it contains moral values such as cooperation, responsibility, tolerance, honesty, and discipline. Third, local cultural practices and traditions can function as valuable learning resources that provide authentic learning experiences and support students’ social awareness and cultural appreciation. This study concludes that local wisdom–based Social Studies learning plays an important role in strengthening character education among elementary school students and should be implemented more systematically in educational practices. Students and should be implemented more systematically in classroom practice. This study contributes to the development of Social Studies education and character education by providing a comprehensive synthesis of previous research on the integration of local wisdom in elementary school learning. The findings enrich the theoretical understanding of local wisdom–based learning as an effective approach to strengthening students’ character values while preserving cultural identity